2013
DOI: 10.1007/s00520-013-1891-7
|View full text |Cite
|
Sign up to set email alerts
|

Phase 1 clinical trials in end-stage cancer: patient understanding of trial premises and motives for participation

Abstract: Patients with end-stage cancer participating in phase 1 clinical trials are unaware of the very small potential for treatment benefit and the risk of harm. Trial participation may offer hope and social-emotional support and a strategy for coping with the emotional stress associated with advanced cancer and may, consequently, improve emotional well-being.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
118
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 56 publications
(124 citation statements)
references
References 23 publications
5
118
1
Order By: Relevance
“…Some relatives also expressed that they felt like they had no choice . Acceptors believed they would make the same decision again , they felt that trial participation gave them the best treatment available , and they felt that trial participation was an easy decision . Patients knew that they had options, and being able to make their own decisions was very important, even though options were limited .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Some relatives also expressed that they felt like they had no choice . Acceptors believed they would make the same decision again , they felt that trial participation gave them the best treatment available , and they felt that trial participation was an easy decision . Patients knew that they had options, and being able to make their own decisions was very important, even though options were limited .…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, other studies revealed that the information was unclear for quite a few patients. Misunderstanding the principle of allocation, confusion about trial setup, potentially equal risks and benefits and trial purpose were common problems.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The rights, safety and well‐being of the participants are protected by the international, ethical and scientific principles of the International Council for Harmonisation of Technical Requirements for Pharmaceuticals for Human Use Good Clinical Practice (ICH GCP), which also stresses the necessity of obtaining the participants’ voluntary informed consent prior to participation in the trial (International Council for Harmonisation of Technical Requirements for Pharmaceuticals for Human Use, ). A 2013 Swedish study directed attention towards ethical concerns regarding cancer patients’ participation in phase I trials because patients in the study often overestimated the benefits and underestimated, or failed to understand, the risks and possible side effects related to treatment in the trial (Godskesen, Nygren, Nordin, Hansson, & Kihlbom, ). As a result, it is essential to examine patients’ perceptions to determine which factors may influence their decision to participate in a clinical drug trial.…”
Section: Introductionmentioning
confidence: 99%